Partisipasi Kaum Bapak dalam Ibadah Gereja - Gracya, Yefta Adri; Lembolangi, Lefran; Parinsi, Niel Kapoginta (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2025)
The low participation of fathers in worship services is a phenomenon observed in many local churches, including in the Getsemani Lempek Congregation. Observations show that many fathers rarely or never attend worship services, whether in church or other fellowship activities. This study aims to identify the factors contributing to the low participation of fathers in worship at the Getsemani Lempek Congregation. The study employed a quantitative method with a descriptive survey approach. The research population consisted of all fathers in the congregation, totaling 27 individuals, selected through total sampling. Data were collected using a closed-ended questionnaire with a four-point Likert scale, validated by expert review and tested for reliability using Cronbach's Alpha (>0.70). Data were analyzed descriptively using SPSS. The results indicate that the main factors causing low participation include heavy work burdens, a sense of underappreciation in worship roles, and family responsibilities that indirectly affect attendance. Other factors such as economic burden, family support, and daily busyness showed lower levels of influence. The study concludes that low participation is closely related to occupational burdens and the weak spiritual awareness of fathers as family leaders, indicating the need for targeted spiritual formation, practical service opportunities, and personal pastoral approaches to enhance their engagement.